Osoby rozwijające się według autystycznego wzorca: ich jakość życia i warunkujące ją komponenty zdrowotne. Perspektywa samorzeczników autyzmu - Drzazga-Lech, Maja; Kłeczek, Monika (Zeszyty Naukowe Katolickiego Uniwersytetu Lubelskiego Jana Pawła II, 2024)
In this paper, we present qualitative data on autistic adults who defined themselves as autism self-advocates. For us, they play the role of social experts. It was important that the participants of our research had developed self-awareness, as it was required to formulate generalisations about their neurodevelopmental minority. The main goal of our study is to construct a model which illustrates the subjective quality of life and its health components, as indicated by research participants. The results presented are critical for autistic people, their caregivers, therapists, co-workers and employers.